Elaboração de um guia de referência com imagens radiográficas para aplicação em exames extraorais odontológicos - Mickus, Joice (2017)
The radiological exams are important resources in aid of drafting a dental diagnosis. However, should only be performed when there is a real clinical indication, since the effects of ionizing radiation on the human body are cumulative. Flaws in the implementation of radiological procedures result in doubtful quality diagnostic images, being necessary, many times, the repetition of exams. In this way, methods to minimize radiological images rejection must be observed. In order to contribute to the reduction of errors of positioning and consequent rejection of imaging examinations in the area of dentistry, this study had as its objective the creation of a reference guide for application in dental extraoral examinations. For the preparation and structuring of this guide, a study was conducted with the aim of identifying the reasons for the rejection of panoramic radiographs in a digital dental radiology service. The study was retrospective and by means of a search in the software of image acquisition, were selected 2306 digital panoramic radiographs, corresponding to 10% of the total number of examinations performed between the years of 2013 and 2015. From the sample, were identified the rejected exams and the causes of rejection. To collaborate with the development of the reference guide, a questionnaire was applied at technical professionals working in the radiology sector where the research was conducted. The questionnaire was attended by nine questions related to routine work in the sector. With the results obtained in the study it was possible to do the preparation of the guide of reference with radiographic images for application in dental examinations.